Peningkatan Branding Produk Melalui Pelatihan Digital Marketing untuk Pengembangan Bisnis pada Pelaku UMKM Kota Lhokseumawe - Rahmaniar; Fuadi; Khairawati; Isfayani, Erna; Wahyuddin; Arliansyah; Jamil, Afwan; Mufid, M. Nuzul (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This community service activity aims to provide knowledge to MSMEs who already have businesses but have not been able to develop their businesses optimally. To overcome this problem in this community service program through digital marketing training. The targets of this community service activity are MSMEs in Lhokseumawe City. This service method is socialization, training, and application of digital marketing which includes: (1) training on the importance of product branding, and how to create product branding. (2) Explanation of how to create branding for products (3) practice of procedures for implementing digital marketing in business development. This community service partnership activity is carried out face to face and because of implementing this activity it is hoped that MSMEs in the city of Lhokseumawe can understand the importance of product branding for business development and the application and benefits of digital marketing for businesses that are being or will be run in any field, be it culinary, fashion or services.